The effect of rib protector garments on trunk kinematics, performance, and perceptions of quarterbacks during an overhand American Football throw - Walker, M. A.; Li, Y.; Samson, C. O.; Simpson, K. J.; Foutz, T.; Brown, C. N. (International Journal of Sports Science, 2020)
Rib protectors may help reduce serious rib injuries to American football quarterbacks or offer additional protection following injury. However, offensive players may not wear them if perceived to hinder athletic performance. The study`s purposes were 1) to determine if stiffness of two rib protector garments affected trunk axial-rotation kinematics and performance of a football throw, and 2) to determine whether perceptions of mobility and performance were altered before and after the throws. Twelve male quarterbacks completed rib protector perception scales before and after maximal effort throws during each rib protector condition: soft-rib, hard-rib, and control (compression shirt). Trunk kinematics, ball speed, throw error, throw time and perception scores of each rib protector were compared to control using non-inferiority testing. Neither rib protector was inferior to control for trunk kinematics or performance measures. 95% confidence interval of difference scores for most kinematic and performance variables included zero. Hard rib mobility was perceived to be inferior before and after the throws compared to control (difference = 23% - 47%). However, individuals responded differently to each rib protector for perception outcome measures. Both rib protectors can be recommended because neither appeared to hinder throw performance or trunk kinematics. It is important that a given individual quarterback is able to select the one that he feels the most comfortable and confident wearing.